The Historical Roots of Family Businesses, the Entail and the Unification of Wealth - Balázs Arató (Journal on European History of Law, 2023)
Historical aristocratic families, as economic units, can in some ways be seen as the forerunners of today’s family businesses. These wealthy families had essentially the same or similar issues and needs in terms of wealth transfer, inheritance and succession as today’s family businesses. The entail (fideicommissum) was the technical legal solution, or legal institution, which enabled the historic aristocratic families to preserve their economic strength from generation to generation, to keep their wealth together and to develop their specific succession arrangements which have survived for centuries. However, prior to the legal declaration of the entail, the enforceability was always a question mark, and it is a problem that family businesses today are still faced with in relation to certain legal instruments and technical solutions in the area of succession. This paper will first review the history of the development of family businesses and then examine the legal institution of the entail and its various forms, drawing parallels between the historical aristocratic families and the family businesses of today, based on essentially identical interests and aspirations.